Rethinking Modernism in The Waste Land by T.S. Eliot through Shakespeare's The Tempest - Bhandari, Prakash; Thapa, Sabita (Crimson Journal of Science and Technology, 2025)
This paper examines how T. S. Eliot’s modernist masterwork The Waste Land can be reimagined through William Shakespeare’s The Tempest. Although the two works are quite different in historical context and literary form, they share deep concerns about the human condition, loss, fragmentation, and the possibility of renewal. Eliot’s poem is a landmark work of 20th century modernism, while The Tempest stands as one of Shakespeare’s most symbolic late plays. Eliot’s writing highlights a deep awareness of literary tradition, often drawing on earlier texts—especially Shakespeare—to express the loss of faith in the modern world. By reading The Waste Land through the lens of The Tempest, this paper claims that Modernism doesn’t just reject tradition; it transforms it to discover new ways of meaning. Using clear language and accessible analysis, the paper explores the thematic connections between the two works, particularly their shared focus on destruction, hope, and spiritual renewal.